(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Breast care is an activity carried out consciously and regularly to maintain breast health during pregnancy with the aim of preparing for lactation at post partum time. The smoothness of breast milk and the comfort of breastfeeding depend on breast care. The purpose of this study was to determine the relationship between breast care and early breastfeeding initiation with breast milk production in postpartum mothers at RSU Melati Perbaungan in 2023. This research is descriptive analytic by using the cross sectional method. The population in this study were all postpartum mothers at General Hospital Melati Perbaungan in 2023. The sampling technique used was total sampling technique. Primary data in this study were obtained by interview and questionnaire, while secondary data were obtained by knowing the number of postpartum mothers. The analysis technique used was univariate analysis and bivariate analysis using the Chi-Square test. The results showed that the table of statistical analysis / test results with X2 test is 10.519b at df = 1, indicating there is a relationship between breast care and breast milk production where the PV value = 0.003. In the table of the results of statistical analysis / test with X2 test, which is 11.429b at df = 1, shows that there is a relationship between early breastfeeding initiation and breast milk production where the PV value = 0.002 is obtained. Thus breast care, early breast feeding initiation with breast milk production are interrelated, and must be owned by post partum mothers. Keywords: Breast Care, Early Breastfeeding, Initiation, Breast Milk Expulsion.